Character Education Management Strategy as a Solution to the Moral Crisis in Elementary Schools - Endah Saraswati; Bambang Sudarsono; Enung Hasanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The decline in discipline, honesty, and responsibility among elementary school students demonstrates the need for a more focused approach to character education. This study examines the practice of character education management as an effort to address students' moral problems through the POAC management function approach. The study was conducted using a qualitative method using a case study design at Muhammadiyah Elementary School in the Colombo Complex. Data were obtained through interviews, observations, and document reviews, then analyzed interactively using triangulation to validate the data. The research findings indicate that character strengthening is implemented through planning based on students' moral needs, organizing the roles of all school members, implementing value inculcation in learning activities and school life, and ongoing supervision through monitoring and follow-up of student behavior. The implementation of these management functions creates a more systematic and sustainable character education pattern, thus contributing positively to reducing students' moral problems in elementary schools.